2012
DOI: 10.1177/1049909112452625
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care in Muslim Brain-Dead Patients

Abstract: In Muslim patients, the concept of terminal withdrawal and organ donation after brain death is still not well accepted. Future multicenter studies, involving palliative teams, should focus on improving these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…In a retrospective review of braindead Muslim patients, 12% were treated with expectant terminal extubation; after being declared braindead, and 5% still remained “full code” (Khalid et al, 2013). In structured interviews, Shiite scholars stated that the responsibility of passing the final verdict regarding life-saving therapy should be taken by those who were well-informed about saving lives, implying that physicians were best positioned in this regard (Mobasher et al, 2014).…”
Section: Advance Directives and Treatment Discontinuation (See Table 1)mentioning
confidence: 99%
“…In a retrospective review of braindead Muslim patients, 12% were treated with expectant terminal extubation; after being declared braindead, and 5% still remained “full code” (Khalid et al, 2013). In structured interviews, Shiite scholars stated that the responsibility of passing the final verdict regarding life-saving therapy should be taken by those who were well-informed about saving lives, implying that physicians were best positioned in this regard (Mobasher et al, 2014).…”
Section: Advance Directives and Treatment Discontinuation (See Table 1)mentioning
confidence: 99%
“…Two patients remained full code due to family opposition, and the remainder had orders to not attempt resuscitation with life-sustaining therapies. 64,65 Others have rejected the diagnosis over potential confl icts of interest with issues of organ donation. [66][67][68] For example, Egypt experienced an intense ethical reaction against deceased donor transplantation and the notion of brain death following the procurement of organs from executed prisoners under controversial conditions.…”
Section: Dissenting Opinionmentioning
confidence: 99%
“…intensivists reported low comfort in legal, ethical, and religious considerations. Although the majority of Islamic Scholars acknowledge brain death as true death and permit organ donation [37], it has been shown that Muslim families frequently reject brain death and refuse organ donation [38]. World Brain Death Project recommends that healthcare providers be trained in cultural sensitivity and communication [32].…”
Section: Discussionmentioning
confidence: 99%